Physical Activity and Depression during Pregnancy: A Scooping Review - Wee, Bee Suan; Marhazlina, Mohamad; Mohd Razif, Shahril; Lua, Pei Lin; Rosliza, Yahaya; Ain Widad, Abdullah (2019)
Background: Physical activity is considered a proper approach for physical and emotional health improvement and maintenance. A rising body of proof defends the claim that physical activity improves physical and mental health through down-regulation of the hypothalamic pituitary adrenal and sympathetic nervous system. Physical activity plays an important role in the improvement and maintenance of physical and mental health. Objectives: To identify the effect of physical activity in reducing depression symptoms during pregnancy through scoping review. Method: A scoping review of English academic journals based on Arskey and O’Malley (2005) methodology framework was conducted by using three electronic databases for the period of 2015 to 2019. The review and research articles which tested the effect of any type of physical activityor exercise measured during pregnancy on depression or depressive symptoms were included. However, articles on pregnancy related diseases such as gestational diabetes mellitus, hypertension, mental disorder and etc. were excluded. Relevant articles were extracted independently. Result: Among 110 articles of the search results of electronic databases, Scopus (n=39), Ebscohost (n=40), science direct (n=31), only thirty seven studies met our selection criteria after screening, of which includes meta-analysis (n=8), systematic review (n=9), cohort studies (n=11), and intervention (n=9) for antenatal depression. Conclusion: Physical activity during pregnancy reduce depressive symptoms and may prevent depression. Studies focusing on the effect of physical activity on depression during pregnancy and its impact on mother’s mental health are necessary in Malaysia and Asian countries.